PENGARUH MEDIA SOSIAL TERHADAP PENURUNAN MINAT MENIKAH DI KALANGAN GENERASI MUDA (STUDI KASUS PENGGUNAAN APLIKASI MEDIA SOSIAL TIKTOK) - Syarifa Nafla Razania; Sabilul Muhtadin (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2025)
The phenomenon of declining interest in marriage among the younger generation is a social issue that is increasingly sticking out, along with the massive use of social media, especially the TikTok application. This study aims to examine the influence of social media content on young people's perceptions of the institution of marriage, and analyze the role of religiosity in responding to exposure to this information. The approach used is qualitative with a case study method, involving informants aged 15-25 years who actively use TikTok. The results of the study show that TikTok's algorithm that presents content in a repetitive manner based on user preferences can reinforce negative perceptions of marriage, especially through narratives of trauma, divorce, and household conflict. This leads to anxiety, doubt, and even reluctance to get married. However, strong religiosity has been shown to act as a moral and emotional filter in responding to digital content, and is able to encourage individuals to be critical and selective. Therefore, it is necessary to increase digital literacy and strengthen religious values to form a balanced and wise mindset in facing the unstoppable flow of social media information.